2010
DOI: 10.1093/jnci/djp468
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial: Quitline Specialist Training in Gain-Framed vs Standard-Care Messages for Smoking Cessation

Abstract: ResultsSpecialists providing gain-framed counseling used gain-framed statements statistically significantly more frequently than those providing standard-care counseling as assessed with frequency ratings for the two types of gain-framed statements, achieving benefits and avoiding negative consequences (for achieving benefits, gainframed mean frequency rating = 3.9 vs standard-care mean frequency rating = 1.4; mean difference = Ϫ 2.5; 95% confidence interval [CI] = Ϫ 2.8 to Ϫ 2.3; P < .001; for avoiding negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…This loss-framed attitudinal advantage is contrary to message framing postulates [15] and framed smoking cessation trials conducted among adults (e.g., [16,17]). The divergent reactions to framed messages between these groups may reflect age differences in feelings of dissonance.…”
Section: Discussionmentioning
confidence: 80%
“…This loss-framed attitudinal advantage is contrary to message framing postulates [15] and framed smoking cessation trials conducted among adults (e.g., [16,17]). The divergent reactions to framed messages between these groups may reflect age differences in feelings of dissonance.…”
Section: Discussionmentioning
confidence: 80%
“…[15][16][17][18][19] A recent meta-analysis found that self-help approaches (ie, minimal interventions such as written materials) were the only empirically-supported interventions for preventing smoking relapse. 20 One such self-help intervention was found to be efficacious and cost-effective among recently quit smokers.…”
mentioning
confidence: 99%
“…Messages were gain-framed—the focus was on benefits of quitting rather than risks of not quitting. Gain-framed messages have been found more effective in reducing smoking (Toll et al, 2007; Toll et al, 2010; Rothman et al, 2006). Health brochures were titled ―Quit Smoking and Get Healthy‖ and financial brochures were titled ―Quit Smoking and Save Money.‖ Each had specific information on either heath or financial gains achievable over a day, week, and year.…”
Section: Methodsmentioning
confidence: 99%
“…We followed well-developed methods of message-framing to enhance validity (Toll, 2007; Toll, 2010; Rothman et al, 2006; Schneider et al, 2001). To ensure messages were salient for our target populations, we conducted five focus groups (in English and Spanish) to select the most compelling brochures.…”
Section: Methodsmentioning
confidence: 99%